Patterns and Trends in Cetacean Occurrence Revealed by Shorewatch, a Land-Based Citizen Science Program in Scotland (United Kingdom) - Gutiérrez-Muñoz, Paula; Walters, Alice E. M.; Dolman, Sarah J.; Pierce, Graham J. (Frontiers in Marine Science, 2021)
Shorewatch is a citizen science project, managed by Whale and Dolphin Conservation (WDC), that records the occurrence of cetaceans during regular, standardized watches from a series of locations along the coast of Scotland (United Kingdom). Observer training and a clearly defined protocol help deliver a valuable source of information about cetacean occurrence and activity along the coast. Between 2005–2018, over 52000 watches generated over 11000 sightings of at least 18 cetacean species. Generalized Additive Models based on sightings for the five most commonly sighted species (bottlenose dolphin, harbor porpoise, minke whale, Risso’s dolphin, and common dolphin), at those sites with the longest time series, demonstrated seasonal, geographical and year-to-year differences in their local occurrence and relative abundance. Bottlenose dolphins are mainly present at observation sites located on the east coast of Scotland, being uncommon on the west coast, while harbor porpoise and minke whale are principally present at sites located on the west coast. The seasonality observed in cetacean occurrence is consistent with peak abundance in summer months described by previous studies in the area. Mean depth around the observation sites is the static variable that apparently has the greatest influence on species presence and number of sightings, except for Risso’s dolphin. All the species except bottlenose dolphin showed upward trends in occurrence and number of sightings over the period 2012–2018. Evidence of temporal autocorrelation was found between results from consecutive watches at the same site on the same day as well as between results from consecutive days at the same site. The power to detect declines in local abundance over a 6-year period depends on the underlying sighting rate of each cetacean species, the number of watches performed and the rate of decline. Simulations performed to determine the power to detect a decline suggest that the current intensity of observation effort in some observation sites, of about 2500 watches per year, may offer good prospects of detecting a 30% decline of the most frequently sighted species (95% of the time) over a 6-year period, although a more even distribution of observation effort in space and time is desirable. The data could potentially be used for monitoring and 6-yearly reporting of the status of cetacean populations.